2020
DOI: 10.1016/j.bjoms.2020.08.104
|View full text |Cite
|
Sign up to set email alerts
|

You Have Control: aviation communication application for safety-critical times in surgery

Abstract: High-risk organisations (HRO), including aviation, undergo formal communication training, with emphasis on safety-critical moments. Such training is not widespread or mandatory in healthcare, and while there are many differences both share the 'human element' with circumstances leading to an increased risk of harm. A typical operating theatre consists of an operating surgeon, and an assisting surgeon, roles that may change throughout the course of a procedure. Similarly, a training aircraft or multi-crew cockp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…We recommend the regular use of open questions, avoiding the use of pronouns (eg it, that) and repeat back at safety‐critical times. In this way, it can be confirmed that the message is not only heard but also understood by the receiver 25 …”
Section: The Team Briefmentioning
confidence: 54%
“…We recommend the regular use of open questions, avoiding the use of pronouns (eg it, that) and repeat back at safety‐critical times. In this way, it can be confirmed that the message is not only heard but also understood by the receiver 25 …”
Section: The Team Briefmentioning
confidence: 54%
“…Aviation is totally different in that all essential communication is verbal so pilots and air traffic staff are trained to be clear with no ambiguity. We recommend repeat‐back at safety critical times so it can be confirmed that instructions are not only heard but understood by the receiver 9 . Open questions are also good and can enhance team working and empower others to be involved.…”
Section: How Can Human Factors Improve Patient Safety?mentioning
confidence: 95%
“…We recommend repeat-back at safety critical times so it can be confirmed that instructions are not only heard but understood by the receiver. 9 Open questions are also good and can enhance team working and empower others to be involved.…”
Section: Effective Communicationmentioning
confidence: 99%
“…The use of repeat back at safety-critical times (as happens in aviation) such that instructions are not only heard but understood by the receiver is good practice. 9 Open questions are also good and can enhance team working and empowering others to be involved.…”
Section: Effective Communicationmentioning
confidence: 99%
“…During the COVID‐10 pandemic, the use of personal protective equipment (PPE) can result in verbal instructions and body language not being conferred to other team members. The use of repeat back at safety‐critical times (as happens in aviation) such that instructions are not only heard but understood by the receiver is good practice 9 . Open questions are also good and can enhance team working and empowering others to be involved.…”
Section: What Are Human Factors?mentioning
confidence: 99%